Taming the Beast: Diffusion Method in Nonlocal Gravity - Gianluca Calcagni (Universe, 2018)
We present a method to solve the nonlinear dynamical equations of motion in gravitational theories with fundamental nonlocalities of a certain type. For these specific form factors, which appear in some renormalizable theories, the number of field degrees of freedom and of initial conditions is finite.